Integration of ARAIM technique for integrity performance prediction, procedures development and pre-flight operations - Paternostro, Simone (2018)
Advanced Receiver Autonomous Integrity Monitoring (ARAIM) is a new Aircraft Based Augmentation System (ABAS) technique, firstly presented in the two reports of the GNSS Evolutionary Architecture Study (GEAS). The ARAIM technique offers the opportunity to enable GNSS receivers to serve as a primary means of navigation, worldwide, for precision approach down to LPV-200 operation, while at the same time potentially reducing the support which has to be provided by Ground and Satellite Based Augmented Systems (GBAS and SBAS).